A Framework for Negotiation-Based Sustainable Interoperability for Space Mission Design - Coutinho, C.; Jardim-Goncalves, R.; Cretan, A. (Proceedings of the 7th International Workshop on Enterprise Integration, Interoperability and Networking (EI2N’2012), 2012)
The need to improve the time spent performing space mission feasibility design studies has led the aerospace industry to the adoption of Concurrent Engineering methods. These high-performance concepts parallelise the design tasks, effectively reducing design time, but at the cost of increasing risk and rework. The fragile interoperability in this design environment depends greatly on the seniority of the space domain engineers and their expertise in the space design engineering area. As design studies get more complex, with an increasing number of new domains, systems and applications, terminologies and data dependability, together with growing pressure and need for adaptation, the design interoperability arena becomes extremely hard to manage and control. This paper presents the concept of developing and maintaining strong interoperability nodes between the design domains by providing a framework of cloud-based services dedicated to negotiating and enforcing a sustainable interoperability between high-performance businesses.